Productivity and profitability of soybean (Glycine max) and wheat (Triticum aestivum) genotypes grown in sequence under system of crop intensification - SINGH, RAMESH K; DHAR, SHIVA; DASS, ANCHAL; SHARMA, VINOD K; KUMAR, AMIT; GUPTA, GAURENDRA; KUMAR, BIPIN (The Indian Journal of Agricultural Sciences, 2018)
The field experiment was conducted at the ICAR‒Indian Agricultural Research Institute, New Delhi during kharif and rabi seasons of 2014-15 and 2015-16 to study the productivity and profitability of soybean (Glycine max L.) and wheat (Triticum aestivum L.) genotypes grown under system of Crop Intensification (SCI). Three cultivation methods, conventional, SCI (45 × 45 cm) and SCI (30 × 30 cm) for soybean and conventional, viz. and system of Wheat Intensification (SWI) (20 × 20 cm) and SWI (20 × 10 cm) for wheat were assigned to horizontal-plots and four varieties for each of soybean (Pusa 9712, PS 1347, DS 12-13 and DS 12-5) and wheat (HD 2967, HD 3086, HD 2851 and HD 2894) were assigned to vertical-plots in a strip-plot design and replicated thrice. Soybean and wheat sown under SCI produced larger yield attributes, yields and economic returns compared to conventional method. Significantly higher pods/plant, seeds/pod and 100–seed weight of soybean were obtained from SCI (45 × 45 cm) and SCI (30 × 30 cm) than the conventional. Highest soybean seed yield and net returns were obtained with SCI (30×30cm) than the other cultivation methods. The soybean DS 12-13 and DS 12-5 performed better than the other varietieswith respect to yield attributes, yield and net return. Higher effective tillers/m2, grains/spike, 1000-grain weight; grain,straw and biological yields; net returns and benefit-cost ratio of wheat were found under SWI (20 × 20 cm) compared to conventional method of sowing. Amongst wheat varieties, yield attributes, yield and economic returns were obtained with HD 2967 over remaining varieties. The highest system productivity in terms of wheat-equivalent yield (WEY) (11.62 t/ha and 12.02 t/ha) was recorded at both geometries of SCI and SWI than the conventional method.